UTILIZING POETRY TO ENHANCE STUDENT NURSES’ REFLECTIVE SKILLS: A LITERATURE REVIEW - Deby Kristiani Uligraff (Belitung Raya Foundation, Indonesia, 2019)
The notion of reflective practice has been considered important in healthcare professionals’ practice. In nursing, particularly in developed countries such as the United Kingdom, Canada, Australia, it has been set as a required competence for registration. Some action has been taken to support the achievement of competent and reflective practitioners, including embedding reflection in the nursing pre-registration education curriculum. In the past twenty years, there has been focus on using art-based initiatives to help student nurses to reflect on their clinical experience. Amongst the art forms, poetry has been used as a reflective tool. Many studies found that poetry could be helpful for developing students’ reflective skills. This literature review was conducted to identify the feasibility and promising benefit of using poetry to increase student nurses’ reflective skills. A comprehensive search of the literature and integrative review were undertaken for reviewing and discussing the evidence-based literature that supports the using of poetry as a reflective tool. A critical and narrative approach was undertaken for 16 relevant literature related to the importance of reflection in practice, the promising potential to enhance students’ reflective skills during academic education, and how poetry might promote students’ reflective skills. The literature review showed that using poetry in education have been carried out, and have yielded positive results. It is promising to note that the development of reflective practice, as required to be an attribute of a registered nurse, could be stimulated and achieved by the employment of poetry as a reflective tool in clinical education. The literature review also demostrated that using poetry as a reflective tool in nursing education is both feasible and worthwhile. Therefore, it is proven that using poetry as a means of reflection in an education setting is beneficial and valuable.